Study on the Influence of Initial Water Content on One-Dimensional Freezing Process of the Qinghai-Tibet Silty Clay by Using Digital Image Technology. (23rd July 2022) - Wang, Yongtao; Wang, Boyuan; Pang, Shoude; Hua, Weihang; Ji, Zhiqiang; Wang, Dayan
Abstract : The water content of the foundation soil will change dynamically as a result of rainfall, snowfall, and ground surface evaporation, leading to a significant change in frost heave properties of the foundation soil in cold regions. One-dimensional freezing tests of the Qinghai-Tibet silty clay with three different initial water contents in an open system were carried out using CCD image acquisition technology and computed tomography (CT) scanning technology in combination with the traditional soil freeze-thaw test system. The heat conduct process, cryostructure formation, frost heave development, unfrozen zone consolidation, ice segregation, water migration, and redistribution during soil freezing are studied comprehensively. The results show that increasing the sample's initial water content will lead to the increase of frozen depth, ladder-like cryostructures in vertical sections, more structural polygons in horizontal sections, and also more obvious ice lens segregation, unfrozen zone consolidation, and water migration during the freezing of soil samples.